(untitled) (مجلة العلوم الشاملة, 2024)
Three samples of date (Barnsali, Dagla and Tabouni) were taken from the local market in Al-Zawiya City at the period from ( 2020 / 11 / 1 ) to ( 2021 / 2 / 7 ) to studying the effect of these types of dates on the glycemic index. Total sugar determinations for the three types of dates were carried out in industrial research center in Tajora, Tripoli, were as the following: 38.30% for Barnsali, 58.90% for Dagla and 45.30% for Tabouni. Then the effects of dates on blood sugar compared with standard glucose were done and the means where is the following: 65.00mg/100 ml for standard glucose, 73.07 mg/100 ml for Barnsali, 86.46 mg/100 ml for Dagla and 22.80 mg/100 for Tabouni. While, there were significant differences (p<0.01) between Dagla and Barnsali and also between standard glucose and Tabouni date. On the other hand the Dagla and Barnsali dates showed the highest values of blood sugar. As regard to glycemic index, the sample of Dagla date showed the highest mean (190.96 unit) following by the Barnsali sample (172.00 unit), while the Tabouni date was having the lowest mean (120.38 unit) between all the samples.